IS OTT IN INDIA ‘OVER-THE-TOP’? RE-PRESENTATION, REGULATION AND RELIGIOUS SENTIMENTS IN INDIAN OTT - Dutta, Anmol (AoIR Selected Papers of Internet Research, 2021)
The recent OTT regulation measures in India brings Netflix India and Amazon Prime Video, among other subscription based video platforms under the ambit of Ministry of Information and Broadcasting. Analyzing how negotiations of culture interact with the discourse of ‘protecting sensibilities’ in 21st century India, I argue that the discourse of regulation fabricates “representation” and a ‘global’ Indian identity. Manipulating “the terms of appearance”, these images accused of hurting religious sentiments are ‘framed’ to unwittingly reveal themselves , causing a dent in the post-colonial perception of India being a “country where diverse faiths, languages, and cultures co-exist peacefully within the boundaries of a single peacefully within the boundaries of a single state.” Relaying pre-existing panoptic cultural policing that brings India dangerously close to right-wing nationalist propaganda, I examine the role of “religious sentiments” and the dependence on cultural policing in this precarious political climate. I explore what it would mean to submit or to resist this new reality in the seemingly (in)dependent internet age.